1999
DOI: 10.1007/s004390051061
|View full text |Cite
|
Sign up to set email alerts
|

A common PEX1 frameshift mutation in patients with disorders of peroxisome biogenesis correlates with the severe Zellweger syndrome phenotype

Abstract: Peroxisome biogenesis disorders are a heterogeneous group of human neurodegenerative diseases caused by peroxisomal metabolic dysfunction. At the molecular level, these disorders arise from mutations in PEX genes that encode proteins required for the import of proteins into the peroxisomal lumen. The Zellweger syndrome spectrum of diseases is a major sub-set of these disorders and represents a clinical continuum from Zellweger syndrome (the most severe) through neonatal adrenoleukodystrophy to infantile Refsum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 8 publications
2
36
0
Order By: Relevance
“…To monitor PEX1 function, a primary cell line, heterozygous for the common PEX1 alleles p.G843D and I700fs, was transformed, immortalized, and transfected with a GFP-peroxisome targeting signal 1 (PTS1) reporter. A stable clone was selected; we refer to these cells as PEX1-G843D-PTS1, because the second allele is null (10). We verified that GFP-PTS1 remains predominantly cytosolic in these cells when cultured at 37°C (Fig.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…To monitor PEX1 function, a primary cell line, heterozygous for the common PEX1 alleles p.G843D and I700fs, was transformed, immortalized, and transfected with a GFP-peroxisome targeting signal 1 (PTS1) reporter. A stable clone was selected; we refer to these cells as PEX1-G843D-PTS1, because the second allele is null (10). We verified that GFP-PTS1 remains predominantly cytosolic in these cells when cultured at 37°C (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…Walter et al (3) showed markedly reduced levels (5-15%) compared with wildtype PEX1 in fibroblast lysates from patients homozygous for this mutation and a 2-to 3-fold increase at 30°C. Because PEX1 transcript level in these patients is normal (10), it is likely that the PEX1-p.G843D is misfolded and degraded. PEX1 is an AAA (ATPase associated with diverse cellular activities) ATPase that oligomerizes with PEX6 AAA ATPase and when complexed to PEX26, recycles PEX5 from the peroxisome membrane to the cytosol (11).…”
mentioning
confidence: 96%
“…We screened 25 skin fibroblast cell lines from Australasian patients referred for diagnostic investigation to the National Referral Laboratory for Lysosomal, Peroxisomal and Related Genetic Disorders at the Women's and Children's Hospital, Adelaide. Routine diagnostic tests on cultured fibroblasts, which included determination of very-long-chain fatty acids (VLCFA), dihydroxyacetonephosphate acyltransferase (DHAP-AT), and the proportion of sedimentable catalase, were carried out as previously reported [Paton et al, 1996;Maxwell et al, 1999], and were indicative of a peroxisome biogenesis disorder in each case. Patient cell lines and HEK293T cells were cultured in Dulbecco's Modified Eagle Medium (high glucose), supplemented with 10% fetal bovine serum (FBS) and 100mg/mL penicillin-100U/mL streptomycin (Gibco Invitrogen Corp., Melbourne, Australia).…”
Section: Patient Cell Linesmentioning
confidence: 99%
“…The first of these, the c.1108_1109insA mutation in exon 5, leads to the introduction of a PTC upstream of the sequence encoding the first AAA cassette of the protein. Patient 3822, a compound heterozygote for this mutation and the common c.2097_2098insT (also referred to as I700fs or P740X) mutation [Collins and Gould, 1999;Maxwell et al, 1999], is a severely affected patient with a survival age of just 2.8 months. This combination of mutations is analogous to that of a previously reported patient who was a compound heterozygote for the c.904delG (A302QfsX23, also previously named A302fs) mutation and the c.2097_2098insT mutation; PEX1 mRNA levels in cells from this patient were 10% of normal [Maxwell et al 2002].…”
Section: Novel Pex1 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation